2016
DOI: 10.1186/s12864-016-2920-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of transcriptional start sites in the haloarchaeon Haloferax volcanii based on differential RNA-Seq (dRNA-Seq)

Abstract: BackgroundDifferential RNA-Seq (dRNA-Seq) is a recently developed method of performing primary transcriptome analyses that allows for the genome-wide mapping of transcriptional start sites (TSSs) and the identification of novel transcripts. Although the transcriptomes of diverse bacterial species have been characterized by dRNA-Seq, the transcriptome analysis of archaeal species is still rather limited. Therefore, we used dRNA-Seq to characterize the primary transcriptome of the model archaeon Haloferax volcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
187
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(221 citation statements)
references
References 93 publications
18
187
1
15
Order By: Relevance
“…Data visualization was performed using IGV v2.4.6 [90] and Gaggle Genome Browser [26]. Additionally to Halobacterium salinarum , this genome-wide dataset analysis was performed for: Haloferax volcanii DS2 (PRJNA324298) [8], Methanocaldococcus jannaschii DSM 2661 (PRJNA342613) [91], Thermococcus kodakarensis KOD1 (PRJNA242777) [10] and Thermococcus onnurineus NA1 (PRJNA339284) [92] (Table S10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data visualization was performed using IGV v2.4.6 [90] and Gaggle Genome Browser [26]. Additionally to Halobacterium salinarum , this genome-wide dataset analysis was performed for: Haloferax volcanii DS2 (PRJNA324298) [8], Methanocaldococcus jannaschii DSM 2661 (PRJNA342613) [91], Thermococcus kodakarensis KOD1 (PRJNA242777) [10] and Thermococcus onnurineus NA1 (PRJNA339284) [92] (Table S10).…”
Section: Methodsmentioning
confidence: 99%
“…Abundant transcript signals established pervasive transcription as a general phenomenon, expanding our knowledge on the universe of non-coding RNAs [5]. Genome-wide mapping of transcription start sites (TSS) in diverse prokaryotes has confirmed that many of these signals are not artifacts but bona fide transcripts [68]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2 in the supplemental material). This finding was not surprising, as leaderless transcripts are common to haloarchaea (20,21). An initial analysis was performed in wt cells to assess whether thiamine and/or its metabolic precursors could influence reporter gene expression.…”
mentioning
confidence: 80%
“…sRNAs in bacteria and eukarya play essential roles in transcriptional regulation, chromosome replication, RNA processing and modification, mRNA stability and translation, and even protein degradation and translocation [3][4][5]. Recently, it was discovered that archaeal genomes encode for large numbers of sRNAs and that many of them are responsive to environmental stresses [1, 2,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%